Searching for the gut microbial contributing factors to social behavior in rodent models of autism spectrum disorder. Issue 5 (20th February 2018) - Needham, Brittany D.; Tang, Weiyi; Wu, Wei‐Li
ABSTRACT: Social impairment is one of the major symptoms in multiple psychiatric disorders, including autism spectrum disorder (ASD). Accumulated studies indicate a crucial role for the gut microbiota in social development, but these mechanisms remain unclear. This review focuses on two strategies adopted to elucidate the complicated relationship between gut bacteria and host social behavior. In a top‐down approach, researchers have attempted to correlate behavioral abnormalities with altered gut microbial profiles in rodent models of ASD, including BTBR mice, maternal immune activation (MIA), maternal valproic acid (VPA) and maternal high‐fat diet (MHFD) offspring. In a bottom‐up approach, researchers use germ‐free (GF) animals, antibiotics, probiotics or pathogens to manipulate the intestinal environment and ascertain effects on social behavior. The combination of both approaches will hopefully pinpoint specific bacterial communities that control host social behavior. Further discussion of how brain development and circuitry is impacted by depletion of gut microbiota is also included. The converging evidence strongly suggests that gut microbes affect host social behavior through the alteration of brain neural circuits. Investigation of intestinal microbiota and host social behavior will unveil any bidirectional communication between the gut and brain and provide alternative therapeutic targets for ASD. © 2018 Wiley Periodicals, Inc. Develop Neurobiol 78: 474–499, 2018